Anne of Green Gables - Montgomery, L. M.; Nang ChanYeema (New York, USA Bantam Books, 1998)
Ann, an orphan, arrives at Green Gables by mistake. She love it with the Cuthberts, will they keep her?
Keywords: Adult Fiction